The Influence of Accountability and Transparency of Zakat Collecting Entities on Zakat Fund Receipt - Sulistiana, Heny; Yuhertiana, Indrawati (Management of Zakat and Waqf Journal (MAZAWA), 2025)
Zakat strategically contributes to wealth distribution to reduce poverty and social inequality. Although the trend of zakat collection in Indonesia continues to increase, the accountability and transparency of financial reports of zakat institutions remain a challenge in building the trust of zakat payers. This study uses a quantitative approach, using BAZNAS and LAZ, licensed by the Ministry of Religious Affairs, for 2021–2023 as the subjects. Secondary data in the form of financial and annual reports were analyzed using IBM SPSS. The results show that accountability, financial transparency, and program transparency have a positive effect on zakat fund receipts, while management transparency has only a positive but insignificant effect. These findings emphasize the importance of implementing PSAK 409 standards and developing a systematic and adaptive transparency strategy for the development of information technology to strengthen governance and increase zakat collection.